Investigation of effects of short-term strength training interventions on sport performance in elite male judokas - Osipov, A. Y.; Guralev, V. M.; Lyakh, V. I.; Ratmanskaya, T. I.; Vapaeva, A. V.; Kudryavtsev, M. D. (Journal of Siberian Federal University. Humanities & Social Sciences, 2023)
Sports performance of elite judo athletes is dependent on the high level of technical skills and physical fitness, including strength capacities: power, muscular strength, muscular endurance and other. This study investigated the effects of short-term (4-/6- or 8-week) specific strength interventions on sports performance in male elite judokas. Thirty six elite male judokas (aged 18-22 years) practiced in short-term (4-/6- or 8-week) strength training intervention added to the regular judo training. To determine sports performance, all athletes were evaluated with regards to their performance during the five judo tournaments within three months in post-intervention. The judokas` individual sport performance was evaluated in accordance with guidelines of the German potential analysis system (PotAS). There were significant (p=0.05) differences in sports performance points among the groups in the first judo tournament in favor of judokas, who practiced 4-week strength training intervention. All judokas demonstrated similar mean sports performance points during the second and third judo tournaments. There were significant (p=0.05) differences in sports performance points in favor of judokas, who practiced 6- or 8-week strength training intervention during the fourth and fifth judo tournaments. The short-term (4-/6- or 8-week) strength training interventions are not equally effective to increase sports performance of elite male judokas within three months in post- strength intervention. The final decision for the specific duration (4-/6- or 8-week) of strength training intervention can be decided according to an judoka`s medal challenges during the competition season: high sports performance in near future (during the month) or an increase in sports performance after one-two months.